The Role of Bank Size Mediation Between Capital and Efficiency on Islamic Bank Profitability in GCC Region - Reza Rahmad Marpaung; Ulfi Kartika Oktaviana (MEC-J (Management and Economics Journal), 2026)
Islamic bank operating in GCC region controlled approximately 52.5% of total global Islamic financial asset at the end of 2023. However, this large share of asset has not been accompanied by optimal profitability. The purpose in this study to examine the influence of CAR and CIR on ROA of Islamic bank in GCC region during the period 2020–2024 with placing the role of bank size as a mediating variable. The method applied is quantitative method through causal associative approach. This study utilizes secondary data obtained from annual financial report of 24 Islamic banks in GCC region, which were determined based on purposive sampling techniques. Data processing and analysis were conducted using panel data regression to test the relationships among variables, taking into account the effect of each entity as well as time-series factors using Fixed Effect Model in EViews 12 software, along with sobel test to examine the mediating role of bank size. The result of the first structural analysis CAR was found to have a significant influence on bank size, while CIR showed no. Furthermore, in the second structural analysis CIR and bank size significantly affect ROA, while CAR showed no. The sobel test result show that bank size is unable to mediate the influence of CAR and CIR on ROA. These finding indicate that operational efficiency and bank scale factors in Islamic bank in GCC region play a greater role in determining ROA than capital adequacy level. This study provides insights and serves as a basis for assessing the influence of CAR, CIR, and bank size on ROA of Islamic bank operating in GCC region.